Coke Structure Evaluation for BF Coke Making. Issue 6 (18th August 2018) - Ghosh, B.; Sahoo, B. K.; Niyogi, O. S.; Chakraborty, B.; Manjhi, K. K.; Das, T. K.; Das, S. K.
ABSTRACT: The microscopic structure and texture of coke are intrinsically important to the cold strength indices (M10 and M40 ) and hot strength indices (CRI and CSR) properties of the coke. Traditionally, Blast Furnace (BF) coke is characterized by its composition, porosity, and strength indices. There are different conventional methods for the determination of porosity as well as the structure of coke mass. In the present work, a comparative study was carried out for measurement and interpretation of the coke microstructure using volumetric analysis, image analysis, mercury porosimetry, and X-ray Computed Tomography (CT) scan measurements. The measurement of coke structural parameters based on image analysis provided information on porosity, pore size distribution, pore wall thickness, radius, perimeter, shape, and other structural parameters. Image analysis provided much more structural information on coke as compared to the volumetric method which is desirable for scientific investigation.